Community Partnership Program For Taman Posyandu Cadres with “Growth Easy Box” In Sidorahayu Village, Wagir, Malang - S. Surachmindari; Wahyu Setyaningsih (Jurnal Dedikasi, 2021)
Posyandu activities should consist of optimizing growth and development activities. The development optimization activities carried out are only in the form of playing activities without any efforts to detect early growth and development. This is due to the lack of ability of cadres to stimulate, detect, and intervene early in child development. This community service is carried out to carry out a community partnership program for Taman Posyandu cadres in Sidorahayu Village, Wagir, Malang Regency. Activities are carried out with the target of Taman Posyandu cadres using groups as learning media and mentoring, planning and monitoring and evaluating all activities. The target in the implementation of this activity is 30 cadres of posyandu in Sidorahayu Village, Wagir, Malang Regency. The activity was carried out from July to September 2020. The empowerment activity for Taman Posyandu cadres was carried out using the "Growth Easy Box" which is an educational game tool (APE) which is used as a medium for simple growth and development checks. The results of the activity show that the participation rate of cadre participants is very good, increasing knowledge and skills of cadres in carrying out SDIDTK.